2017
DOI: 10.3389/fped.2017.00118
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Environment Interactions—What Can These Tell Us about the Relationship between Asthma and Allergy?

Abstract: Asthma is a common condition, which is associated with atopy and allergic conditions including hay fever, eczema, and food allergies. Asthma and atopy are both complex conditions where genetic and environmental factors are implicated in causation. Interactions between genetic and environmental factors, likely via epigenetic mechanisms, are widely thought to be important in determining the risk for developing asthma and atopy. The nature of the relationship between asthma and atopy is unclear and the answer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Perinatal environmental factors and gene–environment interactions have been implicated in the development of childhood allergic diseases in addition to genetic factors [17, 18]. In line with our data, previous studies have shown that a high urbanization level was associated with childhood allergic diseases, so-called hygiene theory [19, 20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Perinatal environmental factors and gene–environment interactions have been implicated in the development of childhood allergic diseases in addition to genetic factors [17, 18]. In line with our data, previous studies have shown that a high urbanization level was associated with childhood allergic diseases, so-called hygiene theory [19, 20].…”
Section: Discussionsupporting
confidence: 88%
“…The impact of maternal and perinatal factors on childhood allergic diseases can be attributed to both genetic susceptibility and gene–environment interactions [17]. Indeed, asthma, AR and AR are prevalent atopic disorders of complex etiology, and these three diseases are frequently observed as the atopic march, indicating the potential shared underlying immunological mechanisms among these three allergic diseases [7].…”
Section: Discussionmentioning
confidence: 99%
“…Kauffmann and Demenais 3 and Turner 13 have previously reviewed gene-environment interactions in asthma, and several major examples are described in this review. However, there is currently no estimate of how much these interactions contribute to the final asthma phenotype.…”
Section: Tnf-amentioning
confidence: 99%
“…A recent review on allergic diseases highlighted that several studies exploring GEI in AD exist, yet findings have not been synthesized (e.g. in a systematic review) . Our objective was to perform a systematic review of the evidence for GEI in AD, focusing on interactions with the FLG null genotype, because this is the strongest and most widely replicated AD genetic risk factor, and because the role of filaggrin in skin barrier function provides a priori support for a hypothetical GEI effect.…”
mentioning
confidence: 99%